30, 000 years of landscape and vegetation dynamics in a mid-elevation Andean valley. (15th April 2021) - McMichael, C.N.H.; Witteveen, N.H.; Scholz, S.; Zwier, M.; Prins, M.A.; Lougheed, B.C.; Mothes, P.; Gosling, W.D.
Abstract: The mid-elevation settings of the Andes are important biodiversity hotspots, yet little is known of their long-term ecology or environmental change. Here, we assess 30, 000 years of landscape and vegetation dynamics on an alluvial terrace located in a mid-elevation valley of the Ecuadorian Andes (Campo Libre). We used loss-on-ignition and particle size analysis to reconstruct past river dynamics, charcoal analysis to reconstruct past fire regimes, and phytolith analysis to reconstruct vegetation change through time. Our results show that Campo Libre was a part of the active floodplain system of the Quijos River until 18, 000 cal yr BP. The biggest vegetation change in vegetation at Campo Libre occurred ca. 13, 000 cal yr BP, when the site warmed and dried, transforming the swampy alluvial terrace into a palm forest. As Holocene precipitation increased, the site transformed back into a swamp around 7500 cal yr BP, and it remained that way until maize agriculture began around 4600 cal yr BP. Local and regional fires were absent from the system until regional fires were detected ca. 3300 cal yr BP. By ca. 2700 cal yr BP, maize cultivation became frequent and regular. Climate, tectonic activity, and the human history have shaped the modern vegetation around Campo Libre, although during different periods of the Holocene. Our results demonstrate the ability of phytoliths to reconstruct vegetation change through time, and show that the mid-elevation Andean valley systems were highly dynamic over the last 30, 000 years. Highlights: Campo Libre lacked fire from 30, 000–4000 years ago. Phytoliths document significant vegetation change before and after the Pleistocene-Holocene transition. Palm abundances have varied significantly through the Holocene in mid-elevation Andean forests. Maize cultivation occurred at the study site ca. 4500 years ago.